Infrared spectra of 16O3 in the 900 - 5600 cm−1 range revisited: Empirical corrections to the S&MPO and HITRAN2020 line lists. (December 2021) - Barbe, Alain; Mikhailenko, Semen; Starikova, Evgeniya; Tyuterev, Vladimir
Highlights: Analysis of experimental FTS infrared spectra of 16 O3 ozone between 900 and 5600 cm −1 . Empirical corrections of calculated line positions. Updates of the line list included to S&MPO information system (http://smpo.iao.ru; http://smpo.univ-reims.fr). Abstract: The paper presents the results of the analysis of experimental FTS infrared vibration-rotation spectra of 16 O3 ozone isotopologue recorded in Reims University in the range from 900 to 5600 cm −1, which was used for the current version of the S&MPO database and web-accessible information system (http://smpo.iao.ru; http://smpo.univ-reims.fr). The majority of the reported data is related to the accurate determination of line positions. New parameters of effective Hamiltonian (EH) models for three polyads of vibrational states {(001), (100)}, {(011), (110)} and {(002), (101), (030), (200)} obtained from accurate fits of observed spectra in 900 – 2200 cm −1 range, have also been described. Further, at the higher wavenumber range 2700 – 5600 cm −1, various perturbations in the observed spectra due to accidental ro-vibrational resonances and which have been at the root of a lack of accuracy in certain regions of the previously published line lists were identified. We have applied empirical corrections to line positions and to corresponding energy levels in cases where the EH models did not provide the target accuracy of 10 −3 cm −1 given of more complex polyad structures, which in turn allowed the use of corrected energy levels to compute improved line positions for the hot bands. In terms of line intensities, we publish here the effective dipole moment parameters and the line lists with empirically-determined absolute intensities for the ν1 /ν3 dyad which are consistent with recent ab initio calculations for the strongest bands. For the higher wavenumber range, the empirical corrections are applied for relative intensities of some series of individual transitions in order to improve the simulation of observed spectra. A significant part of the reported data is included in the 2020 release of the HITRAN database.